Media Sosial sebagai Media Informasi Videografi Bagi Generasi Z: Studi Etnografi Virtual pada Akun Instagram @Urrofi - Raadhii Achmad Prwairakusumah; A. Arindawati, Weni; Oky Oxygentry (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The study, "Social Media as Videography Information Platform for Generation Z on Instagram Account @Urrofi," explores how internet technology, particularly on Instagram, has transformed videography enthusiasts' access to information. This is especially true for Generation Z, recognized as "digital natives" due to their proficiency in digital technologies. The @URROFI Instagram account, owned by a content creator, showcases a variety of videography-related videos and aesthetically pleasing photos, providing insights into visual creativity. The research aims to identify the factors influencing Generation Z's preference for the @URROFI account as a source of videography information and to understand how the account effectively delivers valuable content to meet Generation Z's needs. Using qualitative methods with a virtual ethnography approach, data collection involves observation, unstructured in-person and virtual interviews, ethnographic note-taking, and documentation. The Cyber Media Analysis Method (AMS) is employed for data analysis, suitable for virtual ethnography research. The study's findings highlight the factors influencing Generation Z's choice of the Instagram account @URROFI and the strategies used by the account owner to create engaging and relevant content for Generation Z.